Optimization of Transesterification Parameters of Biodiesel Produced from Sword Bean (Cavalia gladiate) Seed Oil - F. B. Salawu; A. A. Otori; K. Mohammed; J. T. Mathew (Journal of Applied Sciences and Environmental Management, 2023)
The subject of this study was to optimize the transesterification parameters of biodiesel produced from sword bean (C. gladiate) using Response Surface Methodology (RSM). Four transesterification parameters (Reaction temperature 55 0C, Catalyst concentration 0.4 wt%, Methanol to oil ratio 4:1 and reaction time 60 min) were optimized. Data obtained revealed that the optimum reaction conditions for the transesterification of C. gladiata seed oil resulted in 92.88% biodiesel yield. Multiple regression analysis produced a quadratic polynomial equation for methylester and a linear relationship was recorded between the observed and predicted value (R2 = 0.9647) with a significant molar ratio and temperature.  The interaction terms of methanol to oil, molar ratio and temperature with reaction time exhibited a positive effect on the methylester yield. The response surface methodology was found to be a suitable technique for optimizing transesterification process and producing biodiesel that meets the ASTM standard.